2008
DOI: 10.1016/j.asieco.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The bilateral J-curve: Turkey versus her 13 trading partners

Abstract: This study empirically analyses bilateral J-curve dynamics of Turkey with her thirteen trading partners using quarterly time series data over the period . Previous studies on the J-curve of Turkey are based on only aggregate data and they reveal mixed results. Short and long-run impacts of the depreciation of Turkish lira on the trade balance between Turkey and her thirteen trading partners are estimated from the bound testing approach and error correction modeling. The empirical results indicate that whilst t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 24 publications
2
51
0
12
Order By: Relevance
“…However, if increase in Lao income leads to rise in the production of import substitute goods, Laos might import less as income increases, yielding a negative estimation for 2  . Therefore, 2  could be negative and positive depend on whether demand side factors dominate supply side or vice versa (Halicioglu, 2008;Shahbaz et al 2011). Similarly, the estimation of foreign income ( 3  ) coefficient could be positive and negative.…”
Section: Theoretical Framework and Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if increase in Lao income leads to rise in the production of import substitute goods, Laos might import less as income increases, yielding a negative estimation for 2  . Therefore, 2  could be negative and positive depend on whether demand side factors dominate supply side or vice versa (Halicioglu, 2008;Shahbaz et al 2011). Similarly, the estimation of foreign income ( 3  ) coefficient could be positive and negative.…”
Section: Theoretical Framework and Empirical Modelmentioning
confidence: 99%
“…According to the conventional approach, currency devaluation improves the trade balance in long-run (Shahbaz et al 2011(Shahbaz et al , 2012a. However, trade balance is worsened in short run initially and then improves which is called that trade balance is followed the J-curve phenomenon (Matesanz and Fugarolas, 2009 (Halicioglu, 2008;Bahmani-Oskooee and Ratha, 2004a). In Asia, there are also some studies of J-curve phenomenon in Asian developing countries (Arora et al 2003 for India;Onafowora, 2003 for Thailand, Malaysia and Indonesia;Shahbaz et al (2011Shahbaz et al ( , 2012a (Kyophilavong, 2009(Kyophilavong, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…2000 yılı sonrasında Türkiye gibi gelişmekte olan ülkelerdeki döviz kuru-ihracat ilişkisini inceleyen çalışmalarda analizlerin ağırlıklı olarak nedensellik ve eş bütünleme testleri üzerine yapıldığı görülmektedir (Arize, Osang ve Slottje, 2000;Kale, 2001;Acaravcı ve Öztürk, 2002;Onafowora, 2003;Narayan, 2004;Şimşek ve Kadılar, 2005;Karagöz ve Doğan, 2005;Yamak ve Korkmaz, 2005;Gül ve Ekinci, 2006;Türkyılmaz, Özer ve Kutlu, 2007;Peker, 2007;Köse, Ay ve Topallı, 2008;Halicioglu, 2008;Altıntaş ve Öz, 2008;Tarı ve Yıldırım, 2009;Adeniyi, Omisakin ve Oyinlola, 2011;Hall ve Diğ., 2011;Çavdar, 2011;Okay, Baytar ve Sarıdoğan, 2012;Taşpın ve Karabulut, 2013;Keskingöz, 2015). Bunun yanında, Zengin (2000) Vektör Otoregresyon Analizi uygulamıştır.…”
Section: Kavramsal çErçeveunclassified
“…Results rejected the J-curve pattern finding a different adjustment path that after devaluations, trade balance initially improved, then worsened, and later improved again in agricultural sectors. Halicioglu (2008) One of the studies that consider the effect of oil prices as we do is those of Irhan, Alacahan and Korap (2011). They followed ARDL bounds testing approach and found that real depreciations improved the trade balance strongly.…”
Section: Marshall-lerner Condition and J-curve Adjustmentmentioning
confidence: 99%
“…After experiencing severe banking and currency crises in November 2000 and February 2001, Turkey abandoned the fixed exchange rate regime and let exchange rates freely float. After this critical decision, the interest in the exchange rate and trade balance relationship for Turkey has not diminished; on the contrary, it has increased by examining the effect of unpredictable currency depreciations on the export and more generally the trade balance performance (Akbostanci, 2004;Yazici, 2006;Halicioglu, 2008;Bahmani-Oskooee & Kutan, 2009). Studies seem to have been more interested in investigating whether the Marshall-Lerner (M-L) condition holds or J-curve adjustments process exists.…”
Section: Introductionmentioning
confidence: 99%